The development of the digestive system in broiler chickens at different levels of selenium into the mixed fodder - O. Sobolev; B. Gutyj; R. Petryszak; I. Golodjuk; O. Naumyuk; O. Petryszak (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки, 2018)
Scientific studies of foreign and domestic scientists convincingly proved that selenium is a vitally necessary trace element for farm animals and birds with a wide range of biological effects. It performs unique multifunctional functions in the body – structural, catalytic, regulatory, possesses antioxidant, anti-carcinogenic radioprotective, immunostimulant, antiviral, anti-mutagenic, anti-toxic and adaptogenic properties, participates in the formation of mechanisms that determine the reproductive function of animals and birds, affects osteogenesis, participates in the processes of growth and development. In the scientific and economic research the influence of additives of various doses of selenium into mixed fodder on the development of the digestive system in broiler chickens was studied. As a source of selenium, selenite sodium was used. The research was conducted in the production conditions on broiler chickens of the COOB 500 cross. The duration of the experiment corresponded to the period of growing the young for meat and was 42 days. It was established that the use of selenium in the composition of mixed fodder for broiler chickens at doses of 0.3; 0.4 and 0.5 mg/kg positively influenced the development of the digestive system in young, in particular, contributed to an increase in the mass (by 4.1–11.6%) and total length (1.3–3.5%) of the intestine in general, and its thin and thick parts in particular, as well as the mass of the muscular stomach (17.3–23.2%) and liver (3.6–10.0%). The best macromorphological parameters of the digestive system development were chicken broilers, which, during the entire period of growing, mixed fodder, were enriched with selenium at a rate of 0.3 mg/kg. Comparison of the live weight of broiler chickens of experimental groups with indicators of intestinal development, muscular stomach and liver allows us to assume that the digestive systems in them have been developed better and during the growing period they function more actively.